Magnesium Oxide Nanoparticles: Effective Agricultural Antibacterial Agent Against Ralstonia solanacearum - Cai, Lin; Chen, Juanni; Liu, Zhongwei; Wang, Hancheng; Yang, Huikuan; Ding, Wei (Frontiers in Microbiology, 2018)
Magnesium (Mg) is an essential mineral element for plants and is nontoxic to organisms. In this study, we took advantage of nanotechnologies to systematically investigate the antibacterial mechanisms of magnesium oxide nanoparticles (MgONPs) against the phytopathogen Ralstonia solanacearum (R. solanacearum) in vitro and in vivo for the first time. R. solanacearum has contributed to catastrophic bacterial wilt, which has resulted in the world-wide reduction of tobacco production. The results demonstrated that MgONPs possessed statistically signiﬁcant concentration-dependent antibacterial activity, and the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were measured as 200 and 250 μg/mL, respectively. Additional studies, aimed at understanding the toxicity mechanism of MgONPs, indicated that physical injury occurred to the cell membranes, along with decreased motility and biofilm formation ability of R. solanacearum, due to the direct attachment of MgONPs to the surfaces of the bacterial cells, which was observed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Reactive oxygen species (ROS) accumulation could also be an important reason for the antibacterial action, inducing DNA damage. The toxicity assessment assay under greenhouse conditions demonstrated that the MgONPs had exerted a large effect on tobacco bacterial wilt, reducing the bacterial wilt index. Altogether, the results suggest that the development of MgONPs as alternative antibacterial agents will become a new research subject.